Cervical cancer screening decentralized policy adaptation: an African rural-context-specific systematic literature review. Issue 1 (1st January 2019) - Rahman, R.; Clark, M. D.; Collins, Z.; Traore, F.; Dioukhane, E. M.; Thiam, H.; Ndiaye, Y.; De Jesus, E. L.; Danfakha, N.; Peters, K. E.; Komarek, T.; Linn, A. M.; et al.
ABSTRACT: Background : Worldwide, nearly 570, 000 women are diagnosed with cervical cancer each year, with 85% of new cases in low- and middle-income countries. The African continent is home to 35 of 40 countries with the highest cervical cancer mortality rates. In 2014, a partnership involving a rural region of Senegal, West Africa, was facing cervical cancer screening service sustainability barriers and began adapting regional-level policy to address implementation challenges. Objective : This manuscript reports the findings of a systematic literature review describing the implementation of decentralized cervical cancer prevention services in Africa, relevant in context to the Senegal partnership. We report barriers and policy-relevant recommendations through Levesque's Patient-Centered Access to Healthcare Framework and discuss the impact of this information on the partnership's approach to shaping Senegal's regional cervical cancer screening policy. Methods : The systematic review search strategy comprised two complementary sub-searches. We conducted an initial search identifying 4272 articles, then applied inclusion criteria, and ultimately 19 studies were included. Data abstraction focused on implementation barriers categorized with the Levesque framework and by policy relevance. Results : Our findings identified specific demand-side (clients and community) and supply-side (health service-level) barriers to implementation of cervical cancer screening services. We identify the most commonly reported demand- and supply-side barriers and summarize salient policy recommendations discussed within the reviewed literature. Conclusions : Overall, there is a paucity of published literature regarding barriers to and best practices in implementation of cervical cancer screening services in rural Africa. Many articles in this literature review did describe findings with notable policy implications. The Senegal partnership has consulted this literature when faced with various similar barriers and has developed two principal initiatives to address contextual challenges. Other initiatives implementing cervical cancer visual screening services in decentralized areas may find this contextual reporting of a literature review helpful as a construct for identifying evidence for the purpose of guiding ongoing health service policy adaptation.